Bioinspired and Ligand‐Regulated Unnatural Prenylation and Geranylation of Oxindoles with Isoprene under Pd Catalysis. (22nd June 2022) - Zhao, Chao‐Yang; Liu, Ying‐Ying; Zhang, Xiang‐Xin; He, Gu‐Cheng; Liu, Heng; Ji, Ding‐Wei; Hu, Yan‐Cheng; Chen, Qing‐An
Abstract: In nature, prenylation and geranylation are two important metabolic processes for the creation of hemiterpenoids and monoterpenoids under enzyme catalysis. Herein, we have demonstrated bioinspired unnatural prenylation and geranylation of oxindoles using the basic industrial feedstock isoprene through ligand regulation under Pd catalysis. Pentenylated oxindoles (with C5 added) were attained with high selectivity when using a bisphosphine ligand, whereas upon switching to a monophosphine ligand, selectivity toward geranylated oxindoles (with C10 added) was achieved. Moreover, the head‐to‐head product could be further isomerized to an internal skipped diene under Pd−H catalysis. No stoichiometric by‐product was formed in the process. Abstract : A practical strategy has been developed for the bioinspired and ligand‐regulated chemoselective unnatural prenylation and geranylation of oxindoles with isoprene under Pd catalysis. The selectivity was governed by modulating the coordination geometry of the Pd catalyst.